A cellulose-based self-healing composite eutectogel with reversibility and recyclability for multi-sensing. (20th October 2022) - Wang, Ying; Fu, Shiyu; Lucia, Lucian Amerigo; Zhang, Hui
Abstract: Flexible sensors have been widely applied in wearable devices recently. These devices are prone to abrasion, crack, and accidental damage, which result in function failure or even abandonment aggravating environmental degradation. Therefore, it is a huge challenge to endow the flexible sensors with self-healability, recyclability as well as high mechanical property. Herein, a novel recyclable, highly stretchable, self-healing eutectogel was fabricated by freeze-thaw of polyvinyl alcohol (PVA), gelatin and dialdehyde carboxymethyl cellulose (DCMC) in a deep eutectic solvent (DES) with strain rate, humid and temperature sensing capability. The composite eutectogel consisted of imine bond and hydrogen bond reversible networks, which endowed the eutectogel with faster self-healability, as well as the green and simple recyclability. It performed satisfying tensile strength (up to ∼1.25 MPa) with unexceptionable fracture elongation (∼1400%). By leveraging the DES to inhibit freezing and dehydration, the eutectogel was fabricated with a wide working temperature (−20.9 to 64.1 °C) while its weight and sensing performance remained stable after 30 days in open air. The composite eutectogel sensor manifested reliable mechanical and electrical properties under repetitive deformation operation and sensitive responsiveness to real-time variation of rate, temperature, and humidity, which well mimics human breathing in time. Amazingly, based on the hydrolysis of the imine and hydrogen bonds, the recyclable eutectogels retained vast majority of mechanical strength, adhesion, and conductivity. Compared to most synthetic soft materials, the composite eutectogels provide a promising strategy for the development of sustainable multifunctional soft materials that have high environmental adaptability and practical applications. Graphical abstract: Image 1